2022
DOI: 10.3148/cjdpr-2022-008
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Roles of Nutrition and Dietetics Professionals in Sustainable Food Systems and Exploring Opportunities for Strategic Collaboration

Abstract: Current food systems drive environmental damage, social injustices, and undermine health, and these challenges are complex and seemingly intractable. Collaboration is required to transition to more sustainable food systems (SFS). Registered Dietitians and Nutritionists (RDs) are an under-leveraged and well-positioned group to contribute to addressing food systems challenges because of their locations in the system and their existing skillsets. Drawing on research with dietitians, this perspective paper present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…49,52,53 More concretely, dietitians working for CSOs can build competence and provide expertise on issues such as the human health and socioecological impacts of different dietary patterns, thus informing the design of policies, programmes and initiatives undertaken by CSOs. In countries such as Canada and Australia, dietitians and their professional associations have advocated for local, regional, state and national policies that contribute to healthy and sustainable food systems, 9 and this is a key area where dietitians and their representative associations could collaborate or align with CSOs in advocacy efforts aimed at strengthening food system governance. Dietitians working in research settings could partner with CSOs to undertake research on food system issues, providing valuable skills on assessing nutrient adequacy and nutritional status and understanding drivers and consequences of food access, consumption and waste, for example.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,52,53 More concretely, dietitians working for CSOs can build competence and provide expertise on issues such as the human health and socioecological impacts of different dietary patterns, thus informing the design of policies, programmes and initiatives undertaken by CSOs. In countries such as Canada and Australia, dietitians and their professional associations have advocated for local, regional, state and national policies that contribute to healthy and sustainable food systems, 9 and this is a key area where dietitians and their representative associations could collaborate or align with CSOs in advocacy efforts aimed at strengthening food system governance. Dietitians working in research settings could partner with CSOs to undertake research on food system issues, providing valuable skills on assessing nutrient adequacy and nutritional status and understanding drivers and consequences of food access, consumption and waste, for example.…”
Section: Discussionmentioning
confidence: 99%
“…This definition encompasses the concepts of economic sustainability (profitable), social sustainability (broad‐based benefits for society) and environmental sustainability (positive or neutral impact on the natural environment). Healthy and sustainable diets contribute to – and are supported by – healthy, sustainable and equitable food systems, 8,9 with the latter defined as ‘the web of actors, processes and interactions involved in growing, processing, distributing, consuming and disposing of foods’ (p. 3) 10 . There is increasing recognition of the role of dietitians in food system transformation, articulated in a growing body of research, resources to guide education and training and position statements on sustainability developed by national dietetics associations 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of SFS‐related learning at the ‘Understand’ and ‘Apply’ levels indicate that in most countries (with NDA membership in ICDA and with dietetic training standards), for most SFS‐related topics, dietitians are not expected to analyse or evaluate situations or processes or contribute to creating solutions for more SFS and dietary patterns. This limits professional capacity in otherwise high‐leverage roles 2 and may result in further distancing of professionals in nutrition and dietetics from their obvious roles in food systems transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary food systems and diets contribute to avoidable, negative effects on morbidity, mortality and public health 1 and are therefore highly relevant to dietitians. Dietitians are well positioned to leverage change throughout food systems 2 and advocate for more sustainability-informed practices, 3,4 such as addressing systemic barriers to healthy food access, designing menus that have lower environmental impacts and working with clients to adopt dietary patterns that are increasingly more sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of this rise, a Food Standards Agency poll found that less than half (48%) of consumers know what a SD consists of, although over half would like to improve their diets to make them more sustainable (54%) (Heard & Bogdan, 2021). Given their education and competencies in food, nutritional adequacy and healthy eating (Pettinger, 2018), nutrition professionals are in a strong position to influence people's choices and food policy (Goodridge et al., 2022; Innes et al., 2018; Mason & Lang, 2018). SD have also been highlighted as a ‘professional growth area’ (Goodridge et al., 2022; Pettinger, 2018).…”
Section: Introductionmentioning
confidence: 99%